PENINGKATAN KETERAMPILAN MENULIS SURAT MENGGUNAKAN PENDEKATAN KONTEKSTUAL DI SEKOLAH DASAR - Muliadi, Muliadi; Halidjah, Siti; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to improve skill on writing letter using contextual approach. The subject of this research is fourth grade students of SD Negeri 04 Aris. The form of this research is descriptive research with classroom action research as the method. The means of this research is to investigate a condition, situation, or other things has been mentioned that the result is exposed in research report because the researcher does not change, add, or manipulate object or research area. The tools of data collecting IPKG I observation sheet, IPKG II observation sheet, Students? observation sheet. In the first cycle, the mean score of students who passed the evaluation test is 72.73% or eight students. In the second cycle, the mean score increase until 81.82% or nine students, and in the third cycle, the mean score is 90.91% or ten students. In conclusion, contextual approach can improve students? skill on writing letter.Keywords: Improving, Writing Skill, Contextual Approach